2013
DOI: 10.1371/journal.pone.0060311
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-Based Vaccines with the Anaplasma marginale MSP1a Functional Motif Induce a Balanced Humoral and Cellular Immune Response in Mice

Abstract: Bovine anaplasmosis is a hemoparasitic disease that causes considerable economic loss to the dairy and beef industries. Cattle immunized with the Anaplasma marginale MSP1 outer membrane protein complex presents a protective humoral immune response; however, its efficacy is variable. Immunodominant epitopes seem to be a key-limiting factor for the adaptive immunity. We have successfully demonstrated that critical motifs of the MSP1a functional epitope are essential for antibody recognition of infected animal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…Thus, it has been successfully applied to identify mimotopes used to diagnose malaria (22) (23) , toxoplasmosis (24) (25) , hepatitis A (26) , neurocysticercosis (27) , strongyloidiasis (28) , thyroid cancer (29) , Chagas' disease (30) , and bovine anaplasmosis (31) , and to develop vaccine candidates against cysticercosis (32) , herpes simplex virus infection (33) , cancer (34) , taeniasis (35) , hepatitis B (36) , trichinellosis (37) , Alzheimer's disease (38) , and bovine anaplasmosis (39) . Phage display technology has been also instrumental in the selection of therapeutic agents to treat various cancers such as glioblastoma, melanoma, leukemia, and prostate and thyroid cancers (40) (41) .…”
Section: Bacteriophages As Tools For the Development Of New Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it has been successfully applied to identify mimotopes used to diagnose malaria (22) (23) , toxoplasmosis (24) (25) , hepatitis A (26) , neurocysticercosis (27) , strongyloidiasis (28) , thyroid cancer (29) , Chagas' disease (30) , and bovine anaplasmosis (31) , and to develop vaccine candidates against cysticercosis (32) , herpes simplex virus infection (33) , cancer (34) , taeniasis (35) , hepatitis B (36) , trichinellosis (37) , Alzheimer's disease (38) , and bovine anaplasmosis (39) . Phage display technology has been also instrumental in the selection of therapeutic agents to treat various cancers such as glioblastoma, melanoma, leukemia, and prostate and thyroid cancers (40) (41) .…”
Section: Bacteriophages As Tools For the Development Of New Vaccinesmentioning
confidence: 99%
“…In another study, three peptides expressed in reactive phage clones and selected against serum from leprosy patients were successfully validated as tools for serological diagnosis of leprosy (44) . A similar approach has been applied to develop diagnostics for other animal and human diseases, such as neurocysticercosis (27) , strongyloidiasis (28) , and bovine anaplasmosis (39) . Phage particles carrying antigenic determinants may be directly used for therapy.…”
Section: Bacteriophages As Tools For the Development Of New Vaccinesmentioning
confidence: 99%
“…Two critical epitopes, STSSQL and SEASTSSQLGA, were identified using phage display technology for identification of immunodominant epitopes recognized by a neutralizing monoclonal antibody against MSP1a (Santos et al, 2012(Santos et al, , 2013. When these epitopes were used as antigen in immunization studies in a mouse model, the number of infected erythrocytes was reduced and mortality was not observed (Santos et al, 2013).…”
Section: Msp1a Diversity and Control Strategies For Bovine Anaplasmosismentioning
confidence: 99%
“…When these epitopes were used as antigen in immunization studies in a mouse model, the number of infected erythrocytes was reduced and mortality was not observed (Santos et al, 2013). However, details of the MSP1a genotype of the A. marginale strain used in the challenge-exposure were not reported or was the variation of this neutralization sensitive peptide among A. marginale strains.…”
Section: Msp1a Diversity and Control Strategies For Bovine Anaplasmosismentioning
confidence: 99%
“…Among them, MSP1a plays an important role in the infection by A. marginale, being associated with the adhesion capacity of rickettsia to the bovine erythrocytes and tick cells (GARCIA-GARCIA et al, 2004), and it has been shown to trigger a protective immune response (BROWN et al, 1998(BROWN et al, , 2001. Recent studies using recombinant MSP1a (rMSP1a) in immunization trials of cattle and laboratory animal models demonstrated an induction of humoral and cellular immune responses associated with an upregulation of pro-inflammatory cytokines (SANTOS et al, 2013;SILVESTRE et al, 2014), suggesting the possibility of its usage in immunization protocols.…”
Section: Introductionmentioning
confidence: 99%